The Influence of Legal Education on Understanding Joint Property in Marriage Among Urban Communities - Rahmat Hidayat; Dina Pratiwi (Indonesian Journal of Islamic Law, 2020)
This research aims to explore the influence of legal education on urban society's understanding of joint property in marriage. The research uses mixed methods, namely a quantitative survey of urban communities and in-depth interviews to gain deeper insight. The research results show that legal education, both formal and non-formal, has a significant influence on legal understanding of joint property. Respondents who received legal education had a better understanding of their rights and obligations regarding joint property, and implemented management practices that were more in line with positive law. These findings indicate the need for increased integration of legal material in the formal education curriculum and the development of non-formal legal education programs that are broader and more inclusive. Recommendations from this research emphasize the importance of collaboration between government, educational institutions and civil society organizations to improve access and quality of legal education, in order to create a more just and legally aware society.